KARAKTERISTIK, TINGKAT NYERI DAN KEMANDIRIAN ACTIVITY DAILY LIVING (ADL) PENDERITA RHEUMATOID ARTHRITIS - Agustine Ramie; Najla Amalia; Mahdalena (Jurnal Keperawatan Priority, 2021)
Rheumatoid Arthritis (RA) is an autoimmune disease, occurs symmetrically in joints. The joints become inflamed which causes swelling, pain, and frequent damage to the inside of the joints. The number of people with RA in the world has exceeded 355 million people. This research aims to describe the independence of activity daily living (ADL) and level of pain. This research was using a descriptive design. The population in this study were all patients with RA, 149 samples were chosen from the population using simple random sampling. The results showed that 84.6% of respondents had independent of their daily living (ADL) activities. As much as 49.7% experienced moderate pain. Respondents who experienced moderate pain were 100% independent in activity daily living (ADL). Meanwhile, 59% of respondents who had severe pain were not independent in daily living activity (ADL). Nurses are needed to help improve the health status of patients with rheumatoid arthritis so that the patient's quality of life can be maintained optimally. Avoid diseases that can aggravate and can meet daily needs independently. Health agencies need to further improve health promotion regarding the maintenance of independence and efforts to overcome pain levels in patients with rheumatoid arthritis.